Representatividade política de minorias sociais identitárias frente aos processos de naturalização estigmatizantes - Nayara Maria de Lima (2024)
The objective of this work is to analyze the obstacles that hinder and impede the development of political representation of identity minorities. To this end, with the help of bibliographical research, a systematic set of reflections was developed, discussing the concept of political representation, studying works that describe elements of political representation and the lack of representation of women as a sign of LGBT political exclusion. It also involves the analysis of subordinated individuals and how the heteronormative standard imposes obstacles that prevent the development of ideal political ambitions and promote gender discrimination in the field of representation. It also proposes as its main objective the analysis of the subordinate individual and its various manifestations in the LGBTQIA+ community, in addition to demonstrating how this phenomenon is reflected in the political sphere, by questioning its representation and political participation. By tracing the brief history of the LGBTQIA+ Movement, the objective is to understand how the positions of these minority groups were consolidated and, thus, analyze, understand and question the relevance of representation and political participation, as well as the social aspects of this group considered a sexual minority. facing heteronormative causes and biases in Brazil.